2012
DOI: 10.1089/dia.2012.0088
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Use of Telemedicine and Self-Monitoring of Blood Glucose via Diabetes Tele Management System (DTMS) to Achieve Target Glycosylated Hemoglobin Values Without Serious Symptomatic Hypoglycemia in 1,000 Subjects with Type 2 Diabetes Mellitus—A Retrospective Study

Abstract: DTMS, based on telemedicine follow-up and multidisciplinary care with SMBG-based monitoring, appears to be safe and cost-effective in the intensive treatment of T2D without serious co-morbidities. This system also avoids limitations of a traditional health care such as the need for very frequent physical visits for each and every drug dose adjustment, diet, and exercise advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 5 publications
2
56
1
2
Order By: Relevance
“…In a tele medicine cohort study on type 2 diabetics by Kesavadev et al (2012), it was determined that the mean±SD A1c value was 8.5±1.4% at the initial visit and was reduced to 6.3±0.6% at 6 months (P<0.0001) [27]. In our study similar to these studies, decreased A1c levels were found at sixth months.…”
Section: Discussionsupporting
confidence: 86%
“…In a tele medicine cohort study on type 2 diabetics by Kesavadev et al (2012), it was determined that the mean±SD A1c value was 8.5±1.4% at the initial visit and was reduced to 6.3±0.6% at 6 months (P<0.0001) [27]. In our study similar to these studies, decreased A1c levels were found at sixth months.…”
Section: Discussionsupporting
confidence: 86%
“…Improved access to quality care and reductions in health care utilization expenses are additional benefits of telehealth technology. Three of the four telehealth cost analysis reviews demonstrated promising benefits with regard to reducing treatment costs and complications for patients living in rural areas (1316). Varied telehealth models are available as an alternative to in-person medical and educational encounters.…”
Section: Resultsmentioning
confidence: 99%
“…Six telehealth models reviewed used an endocrinologist at an urban site working in partnership with a diabetes educator, nurse, or registered dietitian (RD) in a rural location to provide focused DSME (7,1620). Siminerio et al (17) performed behavioral and psychosocial surveys and monitored A1C measures at baseline and after telehealth programs over a 6-month timeframe in the Telemedicine for Reach, Education, Access, and Treatment (TREAT) model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The intervention consisted of a Diabetes Telemanagement System in which a team of physicians, educators, dietitians, nurses, pharmacists, and psychologists provided monitoring functions as well as educational programming and customized guidance for patients in the program. The team maintained electronic records for the patients that included detailed medical history, target glucose values, and life style factors.…”
Section: Telemedicine For Diabetes Managementmentioning
confidence: 99%